The Effect of Using Elsa Speak App for First-Semester Students’ English Speaking Proficiency - Emilia Elsani; Runi Salsabila; Muhammad Fikri Indika Putra; Naba Khilma Nabila; Desi Nahartini (Universitas Pahlawan Tuanku Tambusai, 2023)
In English language learning, achieving adequate and accurate spoken proficiency is crucial. As one of the applications responding to this speaking needs, the ELSA Speak App has become a central tool for language learners. Despite the broader studies on the effectiveness of the ELSA Speak App for secondary school in the literature, less attention has been given to the higher education level study. Considering this condition, the principal objective of this research was to investigate the efficacy of the ELSA Speak App in enhancing English speaking proficiency for students in the Department of English Education UIN Jakarta. Employing a quantitative method, the study selected the pre-experimental design with a nonequivalent pretest-posttest configuration where the performance of one group of 31 students was measured. The study’s findings show that the ELSA Speak App effectively fosters fluency and accuracy enhancements in acquiring EFL students' Speaking skills. Notably, the app stimulates autonomous learning through its key feature, AI instant feedback